Implementing critical thinking methods in Engineering Curriculum - Ashraf, Arselan; Sophian, Ali; Ahmad, Zuraida (2022)
It is the deliberate and skillful process of intentionally and intellectually applying, analyzing, synthesizing and/or evaluating knowledge received through observation, experience, reflection, reasoning and/or communication as a guide to beliefs and actions. The development of critical thinking abilities is emphasized in Islamic teachings and modern educational models and methodologies. When it comes to technological data, engineers are the experts. Engineers are becoming more and more reliant on critical thinking as issues become more complex. Critical thinking in engineering, particularly for students, is the subject of this paper, which emphasizes its importance.